Komentarz do dekretu Trybunału Roty Nuncjatury Apostolskiej w Hiszpanii c. Moran Bustos z dnia 1 kwietnia 2007 roku dotyczący właściwości sądowej w sprawie wniesionej jako nova causae propositio - Białobrzeski, Tomasz (Ius Matrimoniale, 2018)
The decree presented below does not constitute a substantive decision on the declaration of nullity of marriage filed as nova causae propositio. It refers to the question of pre-trial competence of the tribunal, which is to deal with the case in the next instance, when the definitive sentence has already been passed. The conflict arose because two ecclesiastical courts – the Court of the Spanish Rota and the interdiocesan second instance court – recognised their jurisdiction in the case. Eventually, the Supreme Tribunal of the Apostolic Signatura issued the matter, recognising the jurisdiction of the Spanish Rota Tribunal in the referenced case.